1989
DOI: 10.1159/000460917
|View full text |Cite
|
Sign up to set email alerts
|

A New Cellulose Acetate Filter to Remove Leukocytes from Buffy-Coat-Poor Red Cell Concentrates

Abstract: Transfusion of leukocyte-free red cell concentrates (RCC) prevents or delays HLA immunization in multitransfused patients. We investigated a new cellulose acetate filter which was recently introduced to remove leukocytes from buffy-coat-poor RCC. It was found that the filtration time was only 10 min with buffy-coat-poor RCC in saline-adenine-glucose-mannitol (SAG M; n = 23), hematocrit being 62 ± 2% (SD). The red cell loss was 13.5 ± 2.6% and leukocyte removal was more than 99%. Routine filtration in SAG M (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Like other investigators we have found that the cellulose acetate Cellselect filter removes more than 99% of the leukocytes, resulting in LP-RCC containing less than lo6 leukocytes [8][9][10][11]. Although the dead space of the filter is approximately 200 ml, priming and rinsing the filter is adequate with 500 ml of fluid.…”
Section: Discussionsupporting
confidence: 71%
“…Like other investigators we have found that the cellulose acetate Cellselect filter removes more than 99% of the leukocytes, resulting in LP-RCC containing less than lo6 leukocytes [8][9][10][11]. Although the dead space of the filter is approximately 200 ml, priming and rinsing the filter is adequate with 500 ml of fluid.…”
Section: Discussionsupporting
confidence: 71%